Process of Privatization: International Initial Public Offering (IPO) of an Indonesian State-Owned Enterprise (SOE) - Mangkusubroto, Kuntoro (Jurnal Manajemen Teknologi, 2011)
This paper describes process of privatization through international initial public offering (IPO) of an Indonesia State Owned Enterprice (SOE). The case referred to in this paper is PT Tambang Timah, an Indonesian Mining SOE, which previously suffered from fundamental change in the industry but was successfully turned around prior to its IPO. The discussion starts with the background on privatization of SOEs by highlighting the historical policies of Government toward SOEs, environmental changes leading to improving performance of SOEs, and IPO as an alternative to improving SOE's performance. It followed by a summary description of a successful turn-around and privatization of PTTambang Timah as the case example. It concluded with some lessons learned from the process as well as the specific case.Keywords: Initial public offering, PT Tambang Timah, mining